An Experimental and Numerical Investigation for Characteristics of Submerged Hydraulic Jump over Corrugated Beds - Hossam Ali; Ashraf Elhamaimi (Port Said Engineering Research Journal, 2020)
The present study was executed to compare flow parameters of submerged jump under gate using physical and numerical models. Twenty experimental runs were carried out to study the impact of spaced corrugated beds on basic characteristics of submerged hydraulic jump for values of Froude numbers were ranging from 1.5 to 9.5. Experiments were conducted also for smooth bed.  Submerged jump on best spaced corrugated bed depending on experimental runs was simulated by using VOF method in FLUNET Software and k-ε and RNG k-ε turbulent models are used. To simulate a highly transient and turbulent flow conditions a free surface CFD numerical model has been applied. The results revealed that there is a great coincide between experimental and numerical simulation, corrugated beds reduced jump length and sequent depth by average 5.69% and 12.96% respectively, k-ε and RNG k-ε turbulence models have the ability to simulate this phenomenon and finally the RNG k-ε model give results more consistent with laboratory experiments.